(untitled) (International Seven Journal of Health Research, 2025)
The use of iliac crest bone grafts has become one of the main methods of mandibular bone reconstruction, due to factors that include anatomical similarity and resistance to masticatory forces. Several aspects are determinant for the success of this technique, including shape, location, and size of the bone defect; age, medical condition, and oral hygiene of the patient. In addition, the etiology of the fracture should be considered in the prognosis of surgical treatment. Fractures caused by firearm projectiles, for example, tend to result in postoperative infections, due to the contamination of the wound. The present study aims to present the use of iliac crest bone grafts and associated complications through a clinical case report. Patient M.R.S., male, victim of an accident caused by a firearm projectile in 2017, sought the Oral and Maxillofacial Surgery and Traumatology service of the General Hospital of the State of Bahia with pain in the left hemimandible. On physical examination, the patient presented atypical mobility on mandibular manipulation and the presence of a submandibular fistula on the left with serous drainage at milking. Computed tomography showed a bone defect in the mandibular body region with the presence of a fractured reconstruction plate. Reconstruction of the defect was performed with a free iliac crest graft and reconstruction plates. However, the patient developed a graft infection, and its removal was recommended, without further complications. Accurate diagnosis and planning, and good execution of the technique contribute to the success of the procedure. However, associated complications are possible, as with any surgical procedure.